PENGARUH SUKU BUNGA REVERSE REPO RATE DAN INFLASI TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Sektor Keuangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018) - Sandi Rendy Tumundo; Syaikhul Falah; Bill J.C Pangayow (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This research aims to see the influence of the interest rate (reverse) repo rate directly and indirectly through inflation on the return of shares as well as interest rates (reverse) The repo rate to inflation and inflation on the return of shares, the financial sector companies listed on the Indonesia Stock Exchange in June year 2016 to December year 2018.Results showed that the interest rate (reverse) repo rate has no significant effect either directly and indirectly through inflation on return of shares, can be seen from the analysis of the line and calculation of Sobel test in get t count is-3.64 whereas T table is 2.0518 (significance 0.05) then, in the view of T count (-3.64) < T table (2.0518) meaning there is no while the interest rate (reverse) repo rate has a significant effect on inflation in the see of simple regression rates of reverse repo rate against inflation based on T-Test sig value of 0.05 < 0.05, and inflation also significantly and partial impact on the stock return with the value of the significance test T is 0.041. (0.041 < 0.05) and T count2.150 > 2.0518 t tables.